An integrated analytic hierarchy process and life cycle assessment model for nanocrystalline cellulose production - Teh, Khai Chyi (Animo Repository, 2019)
Nanocrystalline cellulose (NCC) is an emerging renewable bionanomaterial obtained from cellulosic materials such as agricultural waste. NCC has many promising applications in the field of pharmaceuticals, chemical, food and personal care. Research on NCC extraction from different cellulosic materials such as wood pulp, coconut fibre, carrot waste and oil palm empty fruit bunch (EFB) via different process routes has been widely reported, but few have been evaluated for environmental aspects using life cycle assessment (LCA). In particular, there has yet to be any LCA study of NCC production from EFB. Therefore, this work aims to identify the best alternative for NCC production from EFB by comparing three different process routes, namely, (i) Acid Hydrolysis I (chlorine bleaching), (ii) Acid Hydrolysis II (chlorine-free bleaching), and (iii) TEMPO-Oxidation. Since conventional LCA focuses only on environmental impact, the results might not be sufficient for the stakeholders in making important decisions. An integrated analytic hierarchy process (AHP) model incorporating LCA is thus developed to evaluate the alternatives based on environmental aspects as well as technical and economic aspects. The LCA results show that Acid Hydrolysis II has the least overall environmental impact. However, using the integrated AHP–LCA model, Acid Hydrolysis I becomes the optimal choice due to superior technical and economic characteristics. © 2019